DEBATE ON REFORMING THE RUSSIAN ACADEMY OF SCIENCES - Vitaly G. Gorokhov (Высшее образование в России)
The key problem of the article is the destiny of Russian science in the light of today’sreforms. The author reflects upon the requirement of matching the science activities with theinternational and domestic “bureaucratic virtual reality”, touches on such themes as real science and pseudoscience, debate between natural scientists and humanities researchers, the importance of a national language for the development of national science.